The "Republic of Moldova" between transition, globalisation and European integration - Figus, A. (Культура народов Причерноморья, 2001)
The Republic of Moldova is situated in south-eastern Europe, between Romania (in the west) and Ukraine (in the north, east and south). Moldova’s population consisted of 4,4 million inhabitants1, on 33,7 thousand square kilometres and the distances between the most northern and the southern points is 350 kilometres and 150 kilometres from west to east. The combination of climate and soil conditions create high yelds of cereals, grapes, tobacco, fruit and vegetables.